2013
DOI: 10.4172/2155-6156.1000319
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Self-Management and Glycemic Control in A Cohort of Children with Type 1 and Type 2 Diabetes

Abstract: Aim: Self-management of diabetes improves glycemic control. The development of a quick, objective questionnaire in the clinic setting may provide data to the clinician caring for the patient in overall evaluation. Objective: We developed a 23 question tool (clinic preparedness score) and administered it to type 1 and 2 (T1DM & T2DM) diabetes patients. Clinicians of patients were surveyed to determine their perception of adherence by patients. A total of 350 T1DM patients and families and 137 T2DM families we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…A 98% agreement-rate was obtained. Because of initial non-agreement about inclusion, 16 (2%) full-text articles were discussed until consensus was reached [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%
“…A 98% agreement-rate was obtained. Because of initial non-agreement about inclusion, 16 (2%) full-text articles were discussed until consensus was reached [15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30].…”
Section: Study Selectionmentioning
confidence: 99%
“…In the medical literature, numerous studies [6][7][8][9][10][11][12] have shown that therapeutic education significantly influences to achieve better control of Diabetes and thus avoid, prevent or delay complications, evidencing unavoidable benefits not only in metabolic and clinical parameters but also in psychosocial aspects. With the publication of the results of the Diabetes Control and Complications Trial, DCCT [13] and in DM2 the UK Prospective Diabetes Study, UKPDS [14]; in which it is emphasized that intensive therapy required greater focus of the patient in everything related to self-control, it was possible to change the focus in the care of the patient with diabetes, which went from being specific measurements of both glycemia and blood pressure to the prevention of complications and intensification of treatment with well-defined metabolic objectives and strict compliance.…”
mentioning
confidence: 99%